2014
DOI: 10.1139/cgj-2013-0448
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of three-dimensional slopes under water drawdown conditions

Abstract: The traditional approaches for evaluating the stability of slopes or earth dams subjected to water drawdown are performed under plane-strain two-dimensional (2D) condition. Three-dimensional (3D) effect is neglected in assessment of the safety of a slope limited by rigid structures or a dam constrained by a narrow valley. Based on the kinematic approach of limit analysis, a 3D rotational failure mechanism is adopted here to investigate the influence of water drawdown on stability of 3D slopes. Several stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Sandstone w s = 0.4034n − 0.0012 R 2 = 0.99 (5) Mudstone w m = 0.6052n − 2.0041 R 2 = 0.93 (6) where w is the water adsorption of the rock specimen, %; n is the porosity of the rock specimen. good linear relationship (Equations (5) and (6)) in both sandstone and mudstone specimens.…”
Section: Effects Of Cyclic Wetting-drying On Water Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sandstone w s = 0.4034n − 0.0012 R 2 = 0.99 (5) Mudstone w m = 0.6052n − 2.0041 R 2 = 0.93 (6) where w is the water adsorption of the rock specimen, %; n is the porosity of the rock specimen. good linear relationship (Equations (5) and (6)) in both sandstone and mudstone specimens.…”
Section: Effects Of Cyclic Wetting-drying On Water Adsorptionmentioning
confidence: 99%
“…Sandstone ws = 0.4034n -0.0012 R 2 = 0.99 (5) Mudstone wm = 0.6052n -2.0041 R 2 = 0.93 (6) where w is the water adsorption of the rock specimen, %; n is the porosity of the rock specimen. As is known, the water storage capacity depends on the porosity of the rock specimens, and water absorption is the external manifestation of the size and distribution of cracks in the rock.…”
Section: Effects Of Cyclic Wetting-drying On Water Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have mostly focused on the rapid drawdown corresponding to embankment dams and slopes rather than the occurrence of this phenomenon in tunneling projects. Researches regarding the effects of water drawdown on the stability of slopes and dams have been done by Viratjandr and Michalowski [4], Yan et al [5], Wang et al [6], Gao et al [7], Song et al [8] Brinkgreve et al [9] and Zieba et al [10]. The limited number of studies on this subject include Atkinson and Mair [11], Bowers et al [12], Addenbrooke [13], Shin et al [2], Anagnostou [14,1], Yoo et al [15], Moon and Fernandez [16], Wanga and Wang [17], Yoo et al [18], Shen et al [19] Xu et al [20], Alonso and Pinyol [21] and Yoo [3,22].…”
Section: Figure 1 Ground Settlement Affected By Rapid Drawdown Durinmentioning
confidence: 99%
“…Viratjandr [6] used the kinematic limit analysis approach to examine the stability of slope subjected to a rapid or slow drawdown. Based on the theory of limit analysis, Gao [7] discussed the three-dimensional effect of slope under the condition of water level plummeting and found that the plane strain analysis was suitable to evaluate the stability of the waterfacing slope when the aspect ratio was greater than 10. Meanwhile, some researchers studied the failure mechanism, the failure mode, and the deformation mechanism of waterfacing slope by large-scale model tests and centrifuge tests [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%